Traffic Movement at Five Intersections on Jamal Abdul-Nasser Street – Sebha - Alhodairi, Ahmed Mohamed Ahmed; Naiel, Asmael Godan; Fakroun, Massoud Ali Ahmed (Journal of Pure & Applied Sciences, 2021)
Jamal Abdul-Nasser is a major trunk road that divides Sebha city into two semi-equal parts. It connects almost all districts with different activities and services in the center of the city. Alongside Jamal Abdul-Nasser Street, exist various types of activities: administrative, educational, commercial, public services and some other activities. Due to its importance, the street carries out the densest traffic movement within the city. This paper tries to study and analyze traffic movement at five intersections on Jamal Abdul-Nasser Street: (1) Al-Nahdha; (2) Khaled Ibn-Al-Walid; (3) Al-Khotoot; (4) Al-Tijari Bank; (5) Al-Zeraie Bank. Selection of the pre-mentioned intersections referred to their importance as converging points to various important activities and land uses. Data required for the study purposes include intersection characteristics, traffic flow characteristics and traffic composition pattern. The results reveal the significance of taking care of the geometric and regulatory aspects that enable the intersections to perform well with regard the smoothness of traffic flow.